Influence of the fixation technique on the mechanical properties of human cancellous bone of the femoral head. (February 2021) - Fischer, Benjamin; Hofmann, Alexander; Kurz, Sascha; Edel, Melanie; Zajonz, Dirk Jörg; Roth, Andreas; Schleifenbaum, Stefan
Abstract: Background: The femoral head is of central importance for the force transmission from the suprapelvic body mass to the lower extremity. However, the condition of the subcortical bone and its mechanical properties in case of pathological changes due to coxarthrosis or femoral head necrosis differ from the healthy condition. Methods: Fresh femoral heads were gathered during hip total endoprosthesis surgeries and cylindrical cancellous bone samples were extracted with a hollow drill. By means of a uniaxial tensile-compression test system, the compressive strength was determined for two different specimen types (fresh and 24 h storage in acetone). Exemplary tests on an exceptionally large femoral head were performed to compare properties of fresh, fresh-deep-frozen and acetone-stored samples. Findings: The deformation behaviour and the material parameters determined were very heterogeneous. For most of the specimens, a destructive material test was successfully carried out, i.e. the compressive strength was determined. The average strength of fresh specimens was slightly higher than that of acetone specimens. On the other hand, the average Young's modulus of the acetone specimens was higher than that of the fresh specimens. Interpretation: The lower Young's moodulus of the fresh samples compared to the acetone samples could indicate a causal effect of the degreasing influence of the acetone. The partly considerable individual differences in compressive strength and failure compression can have patient-specific influencing factors such as constitution and physical fitness as well as causes in the initial pathological condition. Highlights: Acetone decreases the compressive strength of cancellous bone. Acetone significantly increases the modulus of elasticity of cancellous bone. Cancellous bone structure, pore sizes and elasticity show great individual differences.